Beröring och begränsning: Om gränssnittet mellan djur och människa - Van Ooijen, Erik (Tidskrift för litteraturvetenskap, 2021)
Touch and Restriction: On the Human-Animal Interface Climate crisis and mass extinction show the need to reshape our understanding of human culture in relation to non-human lifeforms. The article considers touch as a point where the border between humans and other species may be renegotiated. Three supplementary modes of human thought, which combine explanation, speculation, and imagination, are interrogated in terms of how they each deal with the tactility of cross-species interaction: philosophy, mythical representations in literature and art, and documentary film. Interface is used as a common concept for how bodies remain distinct from each other while also being able to connect with each other. First, I present how the interface is conceptualized in general by philosophers like Derrida, Nancy and Harman, and between humans and animals in particulars by thinkers like Wood and Michaux. Then, I relate the discussion to how two mythical motifs, focusing on instances of erotic touch across species lines, have been represented in literature and visual art: Leda and the swan, and Pasiphaë and the bull. Finally, I move on to two documentary films: Robinson Devor’s Zoo (2007) and Nikolaus Geyrhalter’s Unser täglich Brot (2005). The idea of zoosexual intercourse is contrasted to the distanced violence of the industrial keeping of animals. I suggest how touch show the possibility of a cross-species communion otherwise negated by late-modern industrial capitalism.